ANALYZING CORPORATE OWNERSHIP AND RISK MANAGEMENT PRACTICES IN SRI LANKAN ENTERPRISES - Fernando , Dr. Suren; Perera, Prof. Ranil (International Journal of Current Practice in Management and Leadership (IJCPML), 2024)
Corporate governance plays a pivotal role in mitigating corporate scandals and financial crises that have plagued global economies in recent years. Numerous large companies across the globe, including those in the United States, Europe, and Asia, faced collapse during financial crises, highlighting the importance of effective corporate risk governance. In Sri Lanka, similar business catastrophes occurred primarily in the Banking and Finance Industry between the late 1980s and the early 2000s. Corporate governance measures, such as board structure, compensation structure, and ownership structure, significantly influence a firm’s risk profile, cash flows, size, and regulatory compliance. Ownership structures, in particular, play a crucial role in resolving or exacerbating agency conflicts within firms. Risk and performance are intertwined, leading owners to seek the balance between managing risk and achieving financial success. In response to these crises, countries like the UK and the USA have initiated regulatory frameworks emphasizing the role of corporate governance and risk management. These frameworks offer guidance on internal control mechanisms and board attributes to enhance corporate accountability and reduce the risk of firm insolvency. However, many Asian countries, including Sri Lanka, have yet to implement regulatory frameworks addressing the role of boards in risk management. This study explores the relationship between ownership structures and corporate risk-taking, shedding light on the significance of ownership in shaping a firm’s approach to risk management.